Simulation of Bimetallic Bush Hot Rolling Bonding Process. (13th May 2015) - Tian, Yaqin; Huang, Qingxue
Abstract : Three-dimensional model of bimetallic bush was established including the drive roller and the core roller. The model adopted the appropriate interface assumptions. Based on the bonding properties of bimetallic bush the hot rolling process was analyzed. The optimum reduction ratio of 28% is obtained by using the finite element simulation software MARC on the assumption of the bonding conditions. The stress-strain distribution of three dimensions was research assumptions to interface deformation of rolling. At the same time, based on the numerical simulation, the minimum reduction ratio 20% is obtained by using a double metal composite bush rolling new technology from the experiment research. The simulation error is not more than 8%.